IMPLEMENTASI MODEL BIMBINGAN TEMAN SEBAYA UNTUK MENINGKATKAN KEPERCAYAAN DIRI (TEKNIK PROBLEM SOLVING DALAM PENENTUAN KARIR PADA SISWA KELAS XII MAS HIDAYATUL INSAN) - Alfina Husna; Desi Erawati; Arini Safitri; Salasiah Salasiah (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2024)
Self-confidence in determining one's career is something that often happens and is commonly discussed. Self-confidence is the ability to convince oneself of one's own abilities or the ability to develop positive values, either for oneself or for others. One of the teenage problems that often arise at this time is one related to career determination. Career determination is also influenced by whether or not a person's level of self-confidence is high. This study aims to look at the effect of peer relationships on self-confidence. The role of peers is to provide input in the form of instructions, reprimands, and directions. This study also aims to see the results of the application of peer guidance models to increase self-confidence using problem-solving techniques in determining student careers at MAS Hidayatul Insan Fi Ta'limiddin. This research is a combination of quantitative and qualitative (mixed methods). Qualitative data was obtained from interviews and observations, while quantitative data was obtained from questionnaires. From the results of the first questionnaire (pre-test), it can be seen that there are still many students who do not have a strong level of self-confidence and have not been able to determine their career planning. Furthermore, peer guidance is carried out in order to increase self-confidence and career determination. Based on the results (post-test) about self-confidence in determining students' careers that have been carried out, the results show that the majority have understood the guidance model that has been applied. So the results showed that based on the questionnaire that had been obtained, it was found that there was a low level of confidence in determining a career and experienced a significant increase in self-confidence after being given counseling guidance services in the form of treatment.